UPAYA MENINGKATKAN HASIL BELAJAR IPS MELALUI PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE MAKE A MATCH PADA SISWA KELAS IV SDN RAWAMANGUN 12 PAGI - Talitha Irfansyah, Syahla; Wardatussa'idah, Indah; Dallion E.W, Engga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low social studies achievement of fourth-grade students at SDN Rawamangun 12 Pagi, which was influenced by a teaching process that remained teacher-centered, a lack of active student participation in learning activities, and the limited variety of teaching models and media used. These conditions have resulted in low student learning outcomes, where out of 32 students, only 11 students (34.38%) achieved learning mastery, while 21 students (65.62%) had not yet reached the established minimum passing score (KKTP) of 75. This study aims to improve social studies learning outcomes through the application of the “Make a Match” Cooperative Learning model, supported by acrylic puzzle media, for fourth-grade students at SDN Rawamangun 12 Pagi. This study employs the Classroom Action Research (CAR) method, conducted in two cycles, comprising the stages of planning, implementation of actions, observation, and reflection. The participants in this study consisted of 32 students, comprising 16 boys and 16 girls. Data collection techniques included observation, interviews, documentation, and achievement tests. The results of the study indicate that the implementation of the “Make a Match” Cooperative Learning model, aided by acrylic puzzle media, was able to improve students’ social studies learning outcomes. The percentage of students achieving mastery increased from 40.63% in Cycle I to 87.5% in Cycle II. Additionally, teacher activity increased from 70% to 93%, and student activity increased from 69.17% to 92%.